0209 Aspects of Disordered Neighborhoods Are Associated with Insomnia, Sleepiness, Fatigue and Control Over Sleep. (12th April 2019) - Griffin, Nakayla; Hale, Lauren; Jean-Louis, Girardin; Killgore, William D S; Warlick, Chloe; Alfonso-Miller, Pamela; Grandner, Michael A
Abstract: Introduction: Previous studies showed that disordered neighborhoods experience overall worse sleep quality and that this may play a role in mental/physical health. This study expands this work by examining validated sleep questionnaires of both sleep and neighborhood disorder, and also examining specific neighborhood aspects. Methods: Data from the Sleep and Healthy Activity, Diet, Environment, and Socialization (SHADES) study were used, consisting of N=1, 003 working-age adults age 22-60 in the Philadelphia area. Participants were administered the Neighborhood Disorder Scale which inquired about neighborhood-level graffiti, noisiness, vandalism, neglect, dirtiness, lack of upkeep, loitering, drug use, alcohol use, neighbor problems, crime, people not "watching out" for each other, police presence, lack of safety, and lack of trust among residents. Sleep variables included the Insomnia Severity Index, Epworth Sleepiness Scale, Fatigue Severity Scale, and Brief Inventory of Sleep Control. Linear regression analyses were adjusted for age, sex, race/ethnicity, and household income. Results: Overall neighborhood disorder (mean= 31.2, SD= 8.6, range= 15-60) was associated with more insomnia (B=0.07, 95%CI [0.02, 0.11], p=0.007), more sleepiness (B=0.04, 95%CI [0.004, 0.08], p=0.029), more fatigue (B=0.13, 95%CI[0.03, 0.22], p=0.007), and less control over sleep (B=-0.06, 95%CI[-0.09, -0.03], p<0.0001). Post-hoc analyses examined specific neighborhood items. Insomnia was most robustly associated with loitering, drug use, alcohol use, and crime. Sleepiness was most robustly associated with loitering and problems with neighbors. Fatigue was most robustly associated with noise, neglect, loitering, drugs, and problems with neighbors. Lack of control over sleep was associated with loitering, drug use, problems with neighbors, crime, lack of "watching out, " police, lack of safety, and lack of trust. Conclusion: Residents of neighborhoods with greater levels of disorder experience more insomnia, more sleepiness, more fatigue, and less control over sleep. Specific aspects of neighborhoods may differentially impact sleep health and may play a role in sleep-related physical/mental health. Support (If Any): R01MD011600, R21ES022931